Revisit Homestay in Kuching, Sarawak: The Perspectives of Local and Foreign Tourist - Bernard Ak Stephen Jussem; Jati Kasuma; Hiram Ting; Saida Zainurossalamia ZA; Dio Caisar Darma (Jurnal Manajemen Indonesia, 2022)
The key factors that affect the tourist satisfaction and their motivation to revisit are the homestay attributes such as accessibility, accommodation, amenities, tourist attraction, tourist activities, and food. Therefore, this descriptive research aims to examine the impact of homestay attributes and mediating role of tourist satisfaction on tourist motivation to revisit homestay in Kuching, Sarawak from the perspectives of local and foreign tourists. The quantitative research through a valid and reliable self-administered survey questionnaire was conducted on 269 local visitors and 206 foreign visitors at four Kuching homestays located at Kampung Krokong Bau, Kampung Pueh Sematan, Kampung Annah Rais Padawan, and Kampung Santubong Kuching. The collected data were computed and analysed through SPSS 25 and SmartPLS. Only homestay attributes of tourist attraction, and food and meal are found to have a significant relationship with tourist satisfaction. While, homestay attributes of amenities, and food and meal are found to have a significant relationship with tourist motivation to revisit. The study proved that there is a significant relationship between tourist satisfaction and tourist motivation to revisit. It also proved that tourist satisfaction mediates the relationship between homestay attributes of tourist attraction, and food and meal on tourist motivation to revisit. The findings indicated that homestay attributes in Kuching, Sarawak need to be improved. Given the significant relationship of tourist attraction, amenities, and food and meal, as an index of tourist satisfaction and motivation to revisit, it is necessary that these homestay attributes to be improved. Keywords—homestay; attributes; mediating role; attraction; Sarawak